Effect of acquisition type on industrial development in emerging markets: evidence from China - Yue, Qi; Deng, Ping; Hua, Xing; Jiang, Luan (Journal of Business Economics and Management, 2022)
In this paper, we proposed a model of how corporate acquisition influences industrial performance by exploring industry-level and firm-level ownership characteristics in emerging markets. Based on a database of 1,934 acquisitions of listed firms in China, we examined the relationship between corporate acquisition type and industrial performance and the moderating effects of industrial and firm ownership characteristics. The study generated three major findings: 1) compared with cross-industry acquisitions, intra-industry acquisitions of firms have a stronger positive effect on industrial performance; 2) corporate ownership and industrial ownership variables exert different moderating impact on the relationship between acquisition type and industrial performance; and 3) firm ownership and industrial ownership have a joint moderating effect on the relationship between acquisition type and industrial performance. By conceptually arguing and empirically verifying how multi-level factors influence industrial performance in the context of emerging economies, we contributed to the study of the relationship between the micro-level firm acquisition and the macro-level industrial development in several distinct ways.